The Integration of Forensic Accounting and External Auditing for Reducing the Audit Expectation Gap An Analytical Study on a Sample of Iraqi Universities - Rabab Adnan Al‐Ruba'ei; Ayad Adel Al‐Fayyadh (مجلة الغري للعلوم الاقتصادية والادارية)
Abstract The current study aims at identifying the complementary relationship between forensic accounting and financial auditing to narrow the expectation gap through using the statistical program SPSS to determine the level of research variables and analysis of the results . The is research used the electronic questionnaire method to determine the level of dimensions represented by the independent variables (forensic accounting and external auditing) and the dependent variable (expectations gap). The following results have been found to get a significant and positive correlations relationship between forensic accounting and the expectations' gap, and a significant positive correlations relationship between the financial audit and the expectations' gap, and a significant correlation between forensic accounting and external auditing in the expectations gap. Therefore, the study recommended that there is a need to sensitize users about the role and duties of the traditional auditor in the field of protection and disclosure of financial errors and fraud. This can be achieved by identifying and adjusting the scope of auditors' responsibility in order to absorb judicial accounting.